XiloVR: Preserving Cultural Heritage through a Virtual Reality-Based Woodcutting Simulation - Costa, Samuel Soares Pereira; Miranda, Bianca Mirtes Araújo; Orichuela, Stefane de Assis; Ramos, Everardo Araújo; Bessa, Olavo Fontes Magalhães; Souza, Alyson Matheus de Carvalho (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
Woodcut (in Portuguese, Xilogravura) holds significant historical and cultural importance in the context of Northeast, playing a crucial role in preserving the region’s artistic heritage. Meanwhile, Virtual Reality (VR) emerges as a powerful technology capable of creating immersive environments that simulate real-world activities, offering new possibilities for education, training, and information dissemination. This paper presents the development of an interactive Virtual Reality (VR) environment that explores the educational potential of this technology to promote woodcut as a cultural heritage of Pernambuco. The proposal aims to provide a practical and engaging experience in art creation, innovating teaching methodologies and ensuring the preservation and transmission of knowledge about woodcut to future generations. The project’s implementation is based on the work of master artisan Edilson Oliveira, a young craftsman from Pernambuco, and simulates all stages of artistic creation, integrating contributions from experts to create a highly realistic experience. This approach seeks to preserve and disseminate knowledge about the technique for future generations.